ANALYSIS OF TREND AND VARIABILITY OF SUMMER SEASON VISIBILITY AND TEMPERATURE IN SAHEL ZONE OF NIGERIA - Balarabe, Mukhtar; Saadu, Bello (FUDMA JOURNAL OF SCIENCES, 2020)
The variation of climate in the past on different time scale in Nigeria has generated a lot of concern and is still posing a threat to life and properties. Meteorologist and climatologist in Nigeria are working hard to address this problem. This study assessed the recent trend and variability of summer season`s visibility and temperature for Sahel zone of Nigeria. The long-term (1988-2017) summer seasons meteorological data derived from National Oceanic Atmospheric Agency-National Climate Data Centre (NOAA-NCDC) were used. A significant decreasing trend in visibility and increasing trend in temperature were detected during the entire period of study. The overall averages were 14.71 ± 4.17 km and 24.54 ± 4.19 respectively. The trends were found more significance in the last ten years. The Decades` means are 19.38± 3.05, 13.76 ± 2.09, 10.98 ± 1.28 km and 20.60 ± 4.72◦C, 25.78 ± 2.54 ◦C and 27.25 ± 0.79 ◦C for the first, second and third decades respectively. Standardize anomaly chart revealed that over the period of study, positive visibility anomaly correspond to negative temperature anomaly and vice visa. Their correlation at p< 0.05 significant level showed a negative relationship of 0.54 over the thirty years period. However, decade analysis showed a positive correlation of 0.47 and negative correlations of 0.61 and 0.74 for the first, second and third decades respectively. These suggest that summer season of the recent decades are dustier than the previous ones and that, summer season of the recent decades become hotter than the previous decades